PENGARUH GLOBALISASI DAN KETIMPANGAN PENDAPATAN TERHADAP PEREKONOMIAN INDONESIA - Jihan Nur’aini Tarwadjan; Aprilliantoni, Aprilliantoni (Cahaya Ilmu Bangsa, 2024)
This study examines the impact of globalization and income inequality on the Indonesian economy. Globalization drives economic growth through international trade and foreign investment, but worsens income inequality, especially for low-income groups and the Micro, Small and Medium Enterprises (MSMEs) sector that have difficulty competing in the global market. This inequality has a negative impact on purchasing power and social stability. To reduce the negative impacts, this study recommends income redistribution policies, increasing access to education, and supporting Micro, Small and Medium Enterprises (MSMEs) so that the benefits of globalization can be felt evenly by the entire community.